Gedichte : Griechisch - Deutsch - Theokrit (Sammlung Tusculum, 2014)
Frontmatter -- Inhalt -- I: ΘYPΣIΣ H ΩIΔH -- II: ΦAPMAKEYTPIA -- III: KΩMOΣ -- IV: NOMEIΣ -- V: AIΠOΛIKON KAI ΠOIMENIKON -- VI: BOYKOΛIAΣTAI -- VII: ΘAΛYΣIA -- VIII: BOYKOΛIAΣTAI -- IX: BOYKOΛIAΣTAI -- X: EPΓATINAI H ӨEPIΣTAI -- XI: KYKΛΩΨ -- XII: ΑITHΣ -- XIII: YΛAΣ -- XIV: AIΣXINAΣ KAI ӨYΩNIXOIΣ -- XV: ΣYPAKOΣIAI H AΔΩNIAZOYΣAI -- XVI: XAPITEΣ H IEPΩN -- XVII: EΓKΩMION EIΣ ∏TOΛEMAION -- XVIII: ΕΛENHΣ E∏IӨAΛAMIOΣ -- XIX: ΚHPIOKΛE∏THΣ -- XX: ΒOYKOΛIΣKOΣ -- XXI: AΛIEIΣ -- XXII: ΔIOΣKOYPOI -- XXIII: EPAΣTHΣ -- XXIV: HPAKΛIΣKOΣ -- XXV: ΗPAKΛHΣ ∏POΣ AΓPOIKON -- XXVI: ΛHNAI H BAKXAI -- XXVII: OAPIΣTYΣ -- XXVIII: ΑΛAKATA -- XXIX: ∏AIΔIKA -- XXX: ∏AIΔIKA -- Ε∏IΓPAMMATA -- Anth. Pal. 9,434 -- Anhang